Pilot study of an expert system adviser for controlling general anaesthesia. - Greenhow, S G; Linkens, D A; Asbury, A J (BJA: The British Journal of Anaesthesia, 1993)
RESAC (real time expert system for advice and control), has been developed to advise on the concentration of inhaled volatile anaesthetics during anaesthesia. It merges clinical information and on-line measurements using Bayesian inference and fuzzy logic. This paper describes a clinical trial in seven patients after initial development of the knowledge base and the human computer interface. Evaluation of the performance of RESAC included analysis of questionnaire responses. Anaesthetists were confident enough to follow the dosage advice given by RESAC in most of the patients.